2000
DOI: 10.1073/pnas.98.1.325
|View full text |Cite
|
Sign up to set email alerts
|

Direction of motion discrimination after early lesions of striate cortex (V1) of the macaque monkey

Abstract: Previous studies have established that humans and monkeys with damage to striate cortex are able to detect and localize bright targets within the resultant scotoma. Electrophysiological evidence in monkeys suggests that residual vision also might include sensitivity to direction of visual motion. We tested whether macaque monkeys with longstanding lesions of striate cortex (V1), sustained in infancy, could discriminate visual stimuli on the basis of direction of motion. Three monkeys with unilateral striate co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0
1

Year Published

2001
2001
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 31 publications
1
15
0
1
Order By: Relevance
“…Protocols for anesthesia and post-surgical treatments were as in the first surgery. Surgical methods were similar to those described in detail previously (Rodman et al, 1989;Moore et al, 1996;Moore et al, 2001). Briefly, lesion surgery was performed after removal of the overlying bone and turning a dural flap.…”
Section: Surgical Proceduresmentioning
confidence: 99%
“…Protocols for anesthesia and post-surgical treatments were as in the first surgery. Surgical methods were similar to those described in detail previously (Rodman et al, 1989;Moore et al, 1996;Moore et al, 2001). Briefly, lesion surgery was performed after removal of the overlying bone and turning a dural flap.…”
Section: Surgical Proceduresmentioning
confidence: 99%
“…Huxlin et al (Huxlin et al 2009) reported that similar recovery could be found after large lesions of V1. Moore et al (Moore et al 2001) made striate lesions in monkeys and reported that they could detect the direction of coherent motion so long as the displays were large. However, in this case the lesions were made soon after birth whereas in the study by Huxlin et al the patients suffered lesions as adults.…”
Section: Introductionmentioning
confidence: 99%
“…For example, monkeys that sustain lesions at 5-6 weeks of age can detect and localize stimuli within a cortical 'scotoma' with a greater level of accuracy than monkeys that suffer lesions later 69 . They are also more effective at discriminating differences in the direction of motion of dot fields, but only when the size of the moving field is large 70 . These observations match findings in humans who suffered damage to the primary visual cortex in childhood.…”
Section: Monkey and Human Visual Systemsmentioning
confidence: 99%